Limited role for thermal erosion by turbulent lava in proximal Athabasca Valles, Mars. Issue 11 (21st November 2015) - Cataldo, Vincenzo; Williams, David A.; Dundas, Colin M.; Keszthelyi, Laszlo P.
Abstract: The Athabasca Valles flood lava is among the most recent (<50 Ma) and best preserved effusive lava flows on Mars and was probably emplaced turbulently. The Williams et al. (2005) model of thermal erosion by lava has been applied to what we term "proximal Athabasca, " the 75 km long upstream portion of Athabasca Valles. For emplacement volumes of 5000 and 7500 km 3 and average flow thicknesses of 20 and 30 m, the duration of the eruption varies between ~11 and ~37 days. The erosion of the lava flow substrate is investigated for three eruption temperatures (1270°C, 1260°C, and 1250°C), and volatile contents equivalent to 0–65 vol % bubbles. The largest erosion depths of ~3.8–7.5 m are at the lava source, for 20 m thick and bubble‐free flows that erupted at their liquidus temperature (1270°C). A substrate containing 25 vol % ice leads to maximum erosion. A lava temperature 20°C below liquidus reduces erosion depths by a factor of ~2.2. If flow viscosity increases with increasing bubble content in the lava, the presence of 30–50 vol % bubbles leads to erosion depths lower than those relative to bubble‐free lava by a factor of ~2.4. The presence of 25 vol % ice in the substrate increases erosion depths by a factor of 1.3. Nevertheless, modeled erosion depths, consistent with the emplacement volume and flow duration constraints, are far less than the depth of the channel (~35–100 m). We conclude that thermal erosion does not appear to have had a major role in excavating Athabasca Valles. Key Points: Thermal erosion by turbulent lava is investigated in proximal Athabasca, Mars Modeled erosion depths are far less than the depth of the Athabasca channel Thermal erosion alone does not appear to have formed the Athabasca channel